(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Interactive learning is the main choice in the world of modern education to increase student participation and involvement in the learning process. One popular tool for interactive learning evaluation is the Quizizz platform. This article discusses the implementation of Quizizz as an evaluation medium in interactive learning. We present field research involving teachers and students from several schools over a certain period of time. The research results show that positive responses from teachers and students towards the use of Quizizz play a key role in increasing students’ interest, motivation and attitudes in learning and the effectiveness of learning evaluation.